The Role Of Zinc Sulphate And Omega 3 On The Improvement Of Weight And Speed Conversion Conversion On Tuberculosis Parent Patients At Surabaya Park Hospital, 2015 - Fara Disa Durry; Bambang Wirjatmadi; Merryana Adriani (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2018)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis, can affect almost all organs of the body with the most locations in the lungs. Immunity and high nutrients such as vitamin C, zinc and other antioxidants have shown good effects for infections, including tuberculosis. One effort to help accelerate sputum conversion of people with pulmonary tuberculosis is by supplementation of Zinc Sulphate and Omega 3.